Фактори розвитку регіональної економіки в контексті системної парадигми - Мікловда, В. П.; Латинін, К. І.; Фіалковський, А. Р.; Miklovda, V.; Latynin, K.; Fialkovskyi, A. (Видавництво Львівської політехніки, 2019)
Подано класифікацію факторів із позиції системної парадигми, що дало змогу виокремити кібернетичні та синергетичні чинники та їхню взаємодію в процесі ухвалення управлінського рішення. За ознакою розташування рушійної сили в процесі розвитку як набуття економічною системою нових якостей чинники поділено на форвардні, поточні, анцедентні. Виявлено роль атрактора, точки біфуркації та флук- туації як факторів розвитку регіональної економічної системи. Показано функціональне навантаження кожної групи факторів.

The purpose of this article is to study the essence of the factors influencing the development of the regional economy as a synergistic system, based on their systematization and classification. In the course of the research, the methods of scientific abstraction, causal induction, abstraction, etc. were applied. Factor analysis allows to establish relationships in the economic system and the interdependence of system components. Systematic approach to the factors in modern research allows to combine in practice cybernetics methods as a system of information management with the laws of synergetic as a science of self-development, self-organization and self-study of the system. The development of an economic system as a self-developing synergetic regional system is largely driven by factors that, depending on the stage of system functioning, are divided into antecedent, current, and forward ones. The necessity of underlining these factors is enhanced in the context where the synergistic qualities of an open economic system are combined and with planned managerial influences in terms of strategic management and decision making. Antecedent factors – determinants and conditions that stand at the source of a certain period of the economic system development, performing the functions of the initial impulse, the basis of the possibilities of the system behavior in the course of its functioning. Antecedent factors arise in both cybernetic (financial) and synergetic (human recourses) systems; therefore, combining them makes it possible to increase the efficiency of the development of the regional economy. The currently highlighted factors that emerge and affect the system in the process of its transformation provide development. Current factors are divided into cybernetics, which are consciously used in the process of managing the system based on the information received, as well as synergistic inherent in the systems in the process of their self-development. The most active synergistic factors attributed to the group of current ones are the point of bifurcation and fluctuation. The bifurcation point determines the future path of system development. Fluctuations significantly affect the uncertainty of the behavior of the economic regional system, its homeostatic and stability. Forward factors are ahead of the process of development, determine its path. Such factors include attractors of the self-organized system, which are instruments of synergistic systems, whereby the strategic management of regional economic development acquires the meaning of a future goal. The goal as a forward factor determines the degree of integration of cybernetic approaches with the mechanisms of synergetics in the process of making both strategic and current management decisions.
Factors of the regional economy development in the context of the system paradigm
Keywords: розвиток регіональної економіки; фактор розвитку; управління розвитком; кібернетичний фактор; синергетичний фактор; системний підхід до регіональної економіки; development of regional economy; factor of development; development management; cybernetic factor; synergistic factor; systematic approach to regional economy; 332.02